Pharmacogenetic analysis of belimumab fails to identify robust genetic predictors of efficacy in lupus. Issue 6 (August 2019) - St Jean, Pamela L.; Roth, David A.; McCarthy, Linda C.; Hughes, Arlene R.
Abstract : GlaxoSmithKline (GSK) conducted pharmacogenetic (PGx) analyses to determine whether genetic variants influence response to belimumab treatment in patients with systemic lupus erythematosus (SLE). We conducted an exploratory genome-wide meta-analysis (GWAS) of 10.9 million genetic variants and the efficacy data from 816 belimumab-treated SLE patients in three phase 3 belimumab clinical studies. Two highly correlated variants, rs293983 and rs364370, in the ANO3 (anoctamin 3) gene region were significantly associated with efficacy as measured by the SLE Response Index (SRI4) with a per-T-allele odds ratio (OR) of 2.15 [95% confidence interval (CI): 1.66–2.79, P =8.0×10 −9 ]. In contrast, there was no association with SRI4 response in 577 placebo-treated patients (per-T-allele OR: 0.98; 95% CI: 0.74–1.29, P =0.87). A post-hoc analysis by geographic region revealed a strong SRI4 response signal in 157 belimumab-treated patients from Asia (per-T-allele OR=2.85, 95% CI: 1.41–5.74, P =0.0021). On the basis of this encouraging finding in Asian patients, we conducted a confirmatory analysis of the SRI4 end point in an independent phase 3 study of SLE patients from northeast Asia. We found no evidence of an association between rs293983 and SRI4 response in 204 belimumab-treated patients (per-T-allele OR: 0.90, 95% CI: 0.52–1.57, P =0.64). The inability to replicate the observed GWAS effect suggests this was a false positive result; hence, we failed to identify any genetic variants significantly associated with belimumab efficacy. Abstract : Supplemental Digital Content is available in the text.